THE CONSTRUCTION OF YOUTH CITIZENSHIP LEGITIMACY: FROM SOCIAL ADVOCACY TO DIGITAL CITIZENSHIP - Belandina Liliana Long; Ivan Gideon Fanggidae; Alfandy Florian Manuain; Ardy Yosafat Pandie (RADJA PUBLIKA, 2026)
This study examines how youth citizenship is constructed beyond its formal status by analyzing the multidimensional processes through which young people gain legitimacy as civic actors. The research problem arises from the tendency to view youth merely as “not-yet citizens,” overlooking their active roles in addressing societal issues. The study aims to demonstrate that youth are real citizens who build legitimacy through social participation, digital engagement, and trust-based practices. Using a phenomenological method, this study explores the lived experiences of youth communities, capturing their advocacy initiatives, cross-community collaborations, and use of digital media. Data were collected through interviews, document analysis, and observation, and analyzed through categorization, interpretation, and inductive reasoning. The findings show that social legitimacy is derived from the relevance of issues raised—such as education, environment, gender equality, and human trafficking—and the solidarity built through collaboration. Digital legitimacy is established by utilizing diverse social media platforms as contemporary civic spaces to expand advocacy and visibility. Trust-based legitimacy emerges from practices of egalitarian advocacy, transparency, and sustained solidarity across communities, which enhance both credibility and moral authority. The study concludes that youth citizenship is a dynamic and multidimensional process shaped by the interplay of social, technological, and ethical contexts. It also suggests that further research should explore how digital legitimacy can evolve into tangible influence on public policy and that comparative studies across regions may enrich understandings of global patterns of youth civic practices.